A five coordination Cu(ii) cluster-based MOF and its application in the synthesis of pharmaceuticals via sp3 C–H/N–H oxidative coupling. Issue 16 (21st July 2017) - Tran, Thuan V.; Le, Hanh T. N.; Ha, Hiep Q.; Duong, Xuan N. T.; Nguyen, Linh H.-T.; Doan, Tan L. H.; Nguyen, Ha L.; Truong, Thanh
Abstract : Five coordination sites of Cu(ii ) cluster were found in VNU-18 that showed highly efficient catalytic property for the oxidative C–H activation via N–H bonds. Abstract : Herein, a copper metal–organic framework, termed as VNU-18, containing penta-coordinated sites was successfully synthesized and fully characterized. This material was demonstrated to be an efficient heterogeneous catalyst for the oxidative C–H activation via N–H bonds. The optimized conditions are applicable for the synthesis of pharmaceuticals constructed by α-amino carbonyl skeletons.